A study to compare the usefulness of a careful clinical examination with venous Doppler studies in patients with varicose veins - Ummer, Sameer Babu; Kanchana, B. (International Surgery Journal, 2018)
Background: The significance of recognizing and locating incompetent perforating veins for treating the patients with varicose vein and venous ulcers is well established. Several methods of diagnosing incompetent perforating veins have been evaluated in the past, however, none show satisfactory accuracy in predicting incompetent perforating veins. Clinical examination with digital palpation of fascial defects is the most widely used method. These fascial clefts are generally thought to keep up a correspondence to incompetent perforating veins. Further evidence is obtained when digital pressure relief on the defect leads to filling of superficial varicose veins or if a tourniquet applied beneath the defect prevents it. The purpose of the present study was to compare clinical examination with that of Doppler venous study in the diagnosis of incompetent perforating veins of lower limbs. Methods: T This is a Cross-sectional comparative study which was carried out in 34 (13 women, 21 men) patients with lower limb varicose veins admitted to the department of general surgery in Aarupadai Veedu medical college and hospital. 38 limbs were studied in 34 patients. They were evaluated by clinical tests and Doppler ultrasound. Results: Saphenofemoral incompetence was correctly diagnosed in all the 38 limbs both by clinical test and Doppler ultrasound. In the evaluation of perforator competency, the sensitivity was 88.14% by clinical tests and 98.31% by Doppler ultrasound. Conclusions: From this study and results, it shows that doppler ultrasound evaluation of the varicose veins should be done for accurate diagnosis in all patients before planning surgery.